PENDAMPINGAN MASYARAKAT DESA SAMBONGGEDE KECAMATAN MERAKURAK KABUPATEN TUBAN UNTUK PENGEMBANGAN DESA MANDIRI - Siregar, Mangihut; Fernandez, Frederik; Alim Tualeka, Basa (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The national development of a country must start from the village, therefore the village plays an important role for the progress of a country. Sambonggede Village is predicated as an independent village. This predicate is obtained based on several results that have been obtained. Usually a village is called an independent village if it has good basic services, adequate infrastructure, easy transportation, good public services, and good governance. In addition to this, a village can be included as an independent village if the Village Development Index (IPD) is more than 75. Therefore, to achieve the predicate of an independent village, especially developing it is not an easy thing but requires extra and creative efforts from various parties, both the community, the government , and other parties. Sambonggede village has become an independent village based on criteria issued by the government. The Sambonggede Village apparatus has succeeded in elaborating several natural and human resources with the community to advance their village. However, there are several elements that have received less attention in this village, one of which is in the agricultural sector. For this reason, it is necessary to provide assistance by motivating farmers and young people who have not yet found work. The service method is carried out by counseling and assisting the community and village officials. The results of the service show that young people together with their parents are willing and proud to be farmers. The profession of a farmer becomes a choice and pride, not because it is forced.